(untitled) (International Journal of Engineering and Computer Science, 2015)
A high-efﬁciency isolated bidirectional ac–dc con- verter is proposed for a 380-V dc power distribution system to control bidirectional power ﬂows and to improve its power con- version efﬁciency. To reduce the switches’ losses of the proposed nonisolated full-bridge ac–dc rectiﬁer using an unipolar switching method, switching devices employ insulated-gate bipolar transis- tors, MOSFETs, and silicon carbide diodes. Using the analysis of the rectiﬁer’s operating modes, each switching device can be selected by considering switch stresses. A simple and intuitive fre- quency detection method for a single-phase synchronous reference frame-phase-locked loop (SRF-PLL) is also proposed using a ﬁlter compensator, a fast period detector, and a ﬁnite impulse response ﬁlter to improve the robustness and accuracy of PLL performance under fundamental frequency variations. In addition, design and control methodology of the bidirectional full-bridge CLLC resonant converter is suggested for the galvanic isolation of the dc distribu- tion system. A dead-band control algorithm for the bidirectional dc–dc converter is developed to smoothly change power conversion directions only using output voltage information. Experimental re- sults will verify the performance of the proposed methods using a 5-kW prototype conveter